Pengaruh Kualitas Pelayanan Paket Ibadah Umrah Reguler Terhadap Kepuasan Jama'ah pada Travel PT. Zam-Zam Wisata Islami - Sarma Hasibuan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of the quality of regular Umrah worship package services on congregational satisfaction at Travel Pt. Zam-Zam Islamic Tourism both partially and simultaneously. This research approach is associative. The population is the entire congregation at Travel Pt. Zam-Zam Islamic Tourism and a sample of 100 Jama'ah at Travel Pt. Zam-Zam Islamic Tourism. Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Testing (t Test). Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00. Partially, service quality has a significant effect on satisfaction.